Personal Social Responsibility Scale for Adolescence: Develop-ment and Psychometric Properties - Kittitas Wancham; Chanakida Thummanond; Laphatphitcha Surawatakul; Dusida Tinmala; Kanit Sriklaub (Qubahan Academic Journal)
Personal social responsibility is extremely crucial to promoting the quality of life and leads to sustainable social development. The promotion of personal social responsibility is particularly important during adolescence, as adolescents start to see the importance of society and prioritize the collective interest over personal ones, which helps them grow into socially responsible adults. Accurate and precise data are essential for promoting personal social responsibility, highlighting the need for reliable measurement tools. This research aims to develop and examine psychometric properties of the Adolescence’s Personal Social Responsibility Scale (APSRS). The APSRS was created in accordance with the personal social responsibility concept by Davis and colleagues. For psychometric properties, item parameters, content validity, construct validity, reliability, and measurement invariance were examined. The participants for the psychometric property’s examination are 600 secondary school students from grades 7 – 12 in Nonthaburi, a province in the metropolitan region of Thailand. The developed APSRS is a five-point Likert scale containing 19 items and is divided into five dimensions, namely economic, legal, environmental, ethical, and philanthropic. The APSRS demonstrates strong psychometric properties and measurement invariance across sexes and educational levels. The APSRS can be used to measure personal social responsibility in adolescents in an accurate and precise way. Its scores can be used to compare the differences of personal social responsibility in adolescents across sexes and educational levels in a meaningful way and with no margin of error. Moreover, the APSRS can be used in various cultural contexts, as many items are based on situations that are culturally neutral and contain general contexts that are not specific to any particular culture.